Strategic Participation of Integrated Thermal and Electrical Energy Service Provider in Natural Gas and Wholesale Electricity Markets - Nasiri, Nima; Zeynali, Saeed; Ravadanegh, Sajad Najafi; Marzband, Mousa (IEEE transactions on industrial informatics, 2023)
The accelerating interest in energy system models has influenced numerous revolutionized alterations in the wholesale gas and electricity market. This article proposes a novel bilevel multifollower optimization framework for the strategic behavior observation of an integrated (thermal and electrical) energy service provider (IESP) as a pricemaker in the wholesale electricity market (WEM) and natural gas market (NGM). At the upper level, the IESP submits offers/bids in WEM and NGM to procure electricity/gas to the customers. To this end, the IESP endeavors to minimize operational costs and influences the market-clearing price (MCP) by deploying demand-side flexibilities, i.e., elastic electrical and thermal loads. At the lower level, the WEM operator and NGM operator receive offers/bids from all market participants and clear the market with the goal of maximizing social welfare. The IESP is modeled via IEEE-33 bus active distribution system and an 8-node district heating system, whereas the WEM and NGMs are embodied by a 6-bus transmission network and a 21-node natural gas network, respectively. Karush-Kuhn-Tucker conditions are introduced to transform the multifollower bilevel optimization problem into a single-level problem, whereas the inherent nonlinearities of the problem are linearized using the theory of strong duality. Moreover, the intrinsic intermittencies of the renewable energy sources is dealt with by the risk-averse information gap decision theory. The results confirm that flexible electrical and thermal demands can diminish the MCP by as much as 4.1%.